NCS Assessments of the Motor, Sensory, and Physical Health Domains - Clark, Jane E.; Pate, Russell; Rine, Rose Marie; Christy, Jennifer; Dalton, Pamela; Damiano, Diane L.; Daniels, Stephen; Holmes, Jonathan M.; Katzmarzyk, Peter T.; Magasi, Susan; McCreery, Ryan; McIver, Kerry; et al. (Frontiers in Pediatrics, 2021)
As part of the National Children’s Study (NCS) comprehensive and longitudinal assessment of the health status of the whole child, scientific teams were convened to recommend assessment measures for the NCS. This manuscript documents the work of three scientific teams who focused on the motor, sensory, or the physical health aspects of this assessment. Each domain team offered a value proposition for the importance of their domain to the health outcomes of the developing infant and child. Constructs within each domain were identified and measures of these constructs proposed. Where available extant assessments were identified. Those constructs that were in need of revised or new assessment instruments were identified and described. Recommendations also were made for the age when the assessments should take place.